Photoionization dynamics of polyatomic molecules - Hockett, Paul (2009)
The work presented in this thesis was carried out with the ultimate aim of learning about the photoionization dynamics of polyatomic molecules. This is a complex problem; in order to obtain sufficient experimental data to shed light on the dynamics careful measurement of photoelectron angular distributions (PADs) is required. Ideally these measurements are rotationally-resolved, and the angular distributions measured correspond to the formation of the molecular ion in a single rotational state. The ionization event, in the dipole approximation, can be completely described by the dipole matrix elements. If sufficient experimental data to determine the radial components of the matrix elements and associated phases, the dynamical parameters, can be obtained the photoionization experiment may be said to be complete. Analysis of such experiments requires that the initial state of the molecular system is also known, to this end resonance-enhanced multi-photon ionization (REMPI) schemes can be used in order to populate a single quantum state prior to ionization. The experiments presented here follow this methodology, with various REMPI schemes used to prepare (pump) and ionize (probe) the molecule under study, and the velocity-map imaging (VMI) technique used to (simultaneously) record the photoelectron spectra and angular distributions.